2020
DOI: 10.20961/jab.v19i2.436
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Karakteristik Pemerintah Daerah, Opini Audit, dan Rasio Kemandirian terhadap Pengungkapan Laporan Keuangan Pemerintah Daerah

Abstract: This study aims to provide evidence of the effect of local government characteristics which consist of population, Human Development Index, audit opinion, and independence ratio on the mandatory disclosure of financial statements of local governments. The sample was local governments in Indonesia in 2017 that meets the criteria. The results of the analysis of 458 local governments in Indonesia showed the average of local governments financial statements disclosure is 60.42%. Furthermore, the results also show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
0
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
3
0
0
7
Order By: Relevance
“…In addition, the results of the data processing on the audit finding variable showed a significance of 0.494, meaning that the audit findings did not significantly influence the level of disclosure of the provincial government financial statements in Indonesia. The results of this study are in line with studies conducted by [11] and [50] revealing that audit findings do not affect the disclosure of regional government financial statements. This implies that a high number of audit findings does not affect the level of disclosure of provincial government financial statements.…”
Section: Multiple Regression Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the results of the data processing on the audit finding variable showed a significance of 0.494, meaning that the audit findings did not significantly influence the level of disclosure of the provincial government financial statements in Indonesia. The results of this study are in line with studies conducted by [11] and [50] revealing that audit findings do not affect the disclosure of regional government financial statements. This implies that a high number of audit findings does not affect the level of disclosure of provincial government financial statements.…”
Section: Multiple Regression Analysissupporting
confidence: 90%
“…This finding was also supported by a study conducted by [3]. However, a different finding was shown by [50] who conducted a study to examine the level of disclosure in regional government financial statements. The results showed that regional wealth does not have a significant effect on the mandatory disclosure in regional government financial statements.…”
Section: Introductionsupporting
confidence: 68%
“…One of the elements needed in increasing the accountability of government financial management is the regional government auditor. This is also supported in the results of Neu, Everett, Rahaman and Martinez (2013), Sargiacomo, Ianni, D'Andreamatteo and Servalli (2015), and Perry and Christensen (2015), Inayatulloh and Siswantoro (2019), Utami and Sulardi (2019).…”
Section: Accountabilitysupporting
confidence: 63%
“…Opini audit adalah pernyataan terkait simpulan pemeriksa kewajaran suatu informasi atau asersi yang dinyatakan pada laporan keuangan (Utami & Sulardi, 2019). Opini audit menjadi indikator atas kebenaran isi laporan keuangan dan kecocokannya dengan aturan yang berlaku.…”
Section: Pendahuluanunclassified